8 rules of love : how to find it, keep it, and let it go [large type] - Shetty, Jay (Center Point Large Print, 2023)
"Nobody sits us down and teaches us how to love. So we're often thrown into relationships with nothing but romance movies and pop culture to help us muddle through. Until now. Instead of presenting love as an ethereal concept or a collection of clichés, Jay Shetty lays out specific, actionable steps to help you develop the skills to practice and nurture love better than ever before. He shares insights on how to win or lose together, how to define love, and why you don't break in a break-up. Inspired by Vedic wisdom and modern science, he tackles the entire relationship cycle, from first dates to moving in together to breaking up and starting over. And he shows us how to avoid falling for false promises and unfulfilling partners. By living Jay Shetty's eight rules, we can all love ourselves, our partner, and the world better than we ever thought possible."--